Restorative Justice Berbasis Kearifan Lokal dalam Penyelesaian Tindak Pidana Ringan di Era Digital - Yeti S. Hasan; Sarlis Mooduto; Nur Lazimatul Hilma Sholehah (Universitas Sebelas Maret, 2025)
Restorative justice (RJ) has emerged as an alternative approach within the criminal justice system, particularly in resolving minor offenses. In Indonesia, RJ practices are closely intertwined with local wisdom that emphasizes consensus, reconciliation, and the restoration of social harmony. However, the digital era presents new challenges, as information technology not only accelerates case resolution but also raises issues of unequal access to justice. This study aims to analyze the practice of restorative justice, grounded in local wisdom, for handling minor criminal offenses and to examine its relevance within the context of legal digitalization in Indonesia. The research employed a qualitative method with a juridical-empirical approach, involving literature review, analysis of statutory regulations, and interviews with law enforcement officials and traditional leaders in Gorontalo. The findings reveal that local wisdom provides social legitimacy for RJ practices, thereby strengthening public acceptance of out-of-court settlements. Furthermore, legal digitalization, through e-justice and e-documentation systems, offers opportunities to expand access and transparency, although it still faces challenges related to infrastructure and digital literacy. This study underscores that integrating local wisdom with digital innovation is a strategic step to optimize the implementation of restorative justice in Indonesia. Therefore, it is crucial to formulate a digital legal framework that is adaptive to local values to promote substantive justice.